2019
DOI: 10.3390/ijms21010266
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Communication in Learning and Memory: From Neuro- and Glio-Transmission to Information Exchange Mediated by Extracellular Vesicles

Abstract: Most aspects of nervous system development and function rely on the continuous crosstalk between neurons and the variegated universe of non-neuronal cells surrounding them. The most extraordinary property of this cellular community is its ability to undergo adaptive modifications in response to environmental cues originating from inside or outside the body. Such ability, known as neuronal plasticity, allows long-lasting modifications of the strength, composition and efficacy of the connections between neurons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 308 publications
(321 reference statements)
1
54
0
Order By: Relevance
“…However, Peng et al [42] argue that despite theoretical limits for an intact xanthone glycoside to cross the blood-brain barrier (BBB), the site-specific opening of this barrier might facilitate the action directly in the brain tissue. Here, we can also speculate that the crude extracts as used traditionally could benefit from saponin presence not only as active compounds but also as adjuvants facilitating targeted distribution of other compounds such as polyphenols via vesicular transport [49].…”
Section: Discussionmentioning
confidence: 90%
“…However, Peng et al [42] argue that despite theoretical limits for an intact xanthone glycoside to cross the blood-brain barrier (BBB), the site-specific opening of this barrier might facilitate the action directly in the brain tissue. Here, we can also speculate that the crude extracts as used traditionally could benefit from saponin presence not only as active compounds but also as adjuvants facilitating targeted distribution of other compounds such as polyphenols via vesicular transport [49].…”
Section: Discussionmentioning
confidence: 90%
“…Physical or chemical microenvironmental changes affect astrocytes' growth and behavior. Changes in astrocytes alter the type of signals they release, therefore altering the microenvironment in a positive or negative manner (Paolicelli et al, 2019;Schiera et al, 2019;You et al, 2020). A study found a novel brain penetrant inhibitor that inhibited the release of vesicles in astrocytes (Rojas et al, 2019).…”
Section: The Relationship Between Astrocyte-derived Evs and Microenvimentioning
confidence: 99%
“…Thus, we assumed that the sought factor(s) could not cross the cell membrane directly but must be contained in extracellular vesicles that are released to the culture medium but destroyed by the freeze-thaw process. It has been demonstrated that neurons as well as glial cells release extracellular vesicles (EVs) of different kinds, both under physiological and pathological conditions (for a review, see [25]).…”
Section: Fbp2 Protein Level In Hippocampal Cells Is Regulated By Extrmentioning
confidence: 99%
“…In turn, the conditioned medium depleted of the vesicle fraction (supernatant) was unable to induce any changes (Figure 7). release extracellular vesicles (EVs) of different kinds, both under physiological and pathological conditions (for a review, see [25]).…”
Section: Fbp2 Protein Level In Hippocampal Cells Is Regulated By Extrmentioning
confidence: 99%